The Difference Of Income On Farm Eucheuma spinosum and Eucheuma cottonii Seaweed In Kutuh Village The District Of South Kuta - SUWARIYATI, NI WAYAN EVI; SUSRUSA, I KETUT BUDI; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2014)
ABSTRACT The Difference Of Income On Farm Eucheuma spinosum and Eucheuma cottonii Seaweed In Kutuh Village The District Of South Kuta This experiment aimed to find out the difference of income on farm Eucheuma spinosum and Eucheuma cottonii seaweed in Kutuh village and the reasons which led farmers is more choose to cultivate Eucheuma cottonii compared Eucheuma spinosum . The method of analysis used in this experiment is a quantitative and qualitative analysis. U test analysis results state that there are significant differences between the income on farm Eucheuma spinosum seaweed with on farm Eucheuma cottonii seaweed in Kutuh village. The average gross farm income Eucheuma spinosum seaweed is Rp 1.217.317,07 whereas Eucheuma cottonii is Rp 2.419.385,07, with the difference is Rp 1.202.068 per 5 are in a one cycle production (45 days). Average net farm income Eucheuma spinosum seaweed Rp 752.426,32 whereas Eucheuma cottonii Rp 1.983.267,99, with the difference is Rp 1.230.841,67 per 5 are in a one cycle production (45 days). The reason farmers seaweed more choose Eucheuma cottonii seaweed among other technical aspects, namely the availability of seeds is more, the economic aspects of the marketing of Eucheuma cottonii seaweed more demand and higher selling prices than Eucheuma spinosum .   Keyword : Eucheuma spinosum, Eucheuma cottonii, income
Keywords: Eucheuma spinosum; Eucheuma cottonii; income